Non-noble-metal-based electrocatalysts toward the oxygen evolution reaction - Wu, Zhi-Peng (2020)
The development of low-cost, high-efficiency, and robust electrocatalysts for the oxygen evolution reaction (OER) is urgently needed to address the energy crisis. In recent years, non-noble-metal-based OER electrocatalysts have attracted tremendous research attention. Beginning with the introduction of some evaluation criteria for the OER, the current OER electrocatalysts are reviewed, with the classification of metals/alloys, oxides, hydroxides, chalcogenides, phosphides, phosphates/borates, and other compounds, along with their advantages and shortcomings. The current knowledge of the reaction mechanisms and practical applications of the OER is also summarized for developing more efficient OER electrocatalysts. Finally, the current states, challenges, and some perspectives for non-noble-metal-based OER electrocatalysts are discussed.